The angiotensin receptor-associated protein Atrap is a stimulator of the cardiac Ca2+-ATPase SERCA2a. Issue 3 (25th March 2016) - Mederle, Katharina; Gess, Bernhard; Pluteanu, Florentina; Plackic, Jelena; Tiefenbach, Klaus-Jürgen; Grill, Alexandra; Kockskämper, Jens; Castrop, Hayo
Abstract: Aims: The angiotensin II type 1 receptor-associated protein (Atrap) is highly expressed in the heart, but its function in the heart is unknown. We hypothesized that cardiac Atrap may interact with proteins other than the AT1 receptor. Methods and results: To identify potential novel interacting partners of Atrap, pull-down assays were performed. Sequencing by MALDI-MS of the isolated complexes showed that Atrap interacts with the cardiac Ca 2+ -ATPase SERCA2a. The interaction between Atrap and SERCA2a was confirmed by co-immunoprecipitation and by surface plasmon resonance (SPR) spectroscopy. Atrap enhanced the SERCA-dependent Ca 2+ uptake in isolated SR membrane vesicles. Furthermore, sarcomere shortenings and [Ca 2+ ]i transients (CaTs) were determined in ventricular myocytes isolated from Atrap−/− and wild-type (WT) mice. The amplitudes of CaTs and sarcomere shortenings were similar in Atrap−/− and WT myocytes. However, the CaT decay and sarcomere re-lengthening were prolonged in Atrap−/− myocytes. To further evaluate the functional relevance of the Atrap-SERCA2a interaction in vivo, left-ventricular function was assessed in WT and Atrap−/− mice. The heart rates (564 ± 10 b.p.m. vs. 560 ± 11 b.p.m.; P = 0.80) and ejection fractions (71.3 ± 1.3 vs. 72 ± 1.8%; P = 0.79) were similar in WT and Atrap−/− mice, respectively ( n = 15 for each genotype). However, the maximum filling rate (d V /d t max ) was markedly decreased in Atrap−/− (725 ± 48 µL/s) compared with WT mice (1065 ± 122 µL/s; P = 0.01; n = 15). Conclusion: We identified Atrap as a novel regulatory protein of the cardiac Ca 2+ -ATPase SERCA2a. We suggest that Atrap enhances the activity of SERCA2a and, consequently, facilitates ventricular relaxation.